Pemberdayaan Masyarakat Sebagai Strategi Pelestarian Alam (Penelitian di Yayasan Konservasi Alam Yogyakarta di Desa Sendangsari Kecamatan Pengasih, Kabupaten Kulonprogo) - , TRI ASTUTI WULANDARI, Drs. Hendrie Adji Kusworo, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The issue of environmental damage is becoming an important issue in development. One way to overcome the environmental problems is conservation. Another problem that arises is the lack of awareness of villagers Sendangsari to safeguard the environment. Yayasan Konservasi Alam Yogyakarta (YKAY) is present as a non-governmental organization engaged in wildlife conservation who then invites the surrounding community to protect the environment and wildlife through empowerment programs. Stages and trends in the empowerment process conducted by YKAY interesting to be studied and understood. This research is qualitative. The unit analysis of this research is targeted community empowerment program YKAY. Research carried out in the region of YKAY, namely in the Village District of Compassionate Sendangsari, Kulon Progo Regency. Informants of this research is the worker of YKAY. Data collection techniques used in this research is the in-depth interviews, observation, and documentation. The findings in the field showed that YKAY as the enabler in the process of empowerment is not through the stages of awareness. This causes the awareness doesnât appear of workers about nature conservation. YKAY begin the process of empowerment from the stages of transformation ability, which is then followed by a phase of increase in intellectual ability. YKAY showed that the absence of this awareness stage instead it can be an example to the workers how to maintain and preserve the surrounding environment. Awareness of workers emerged when the second stage and the third stage is done. Although not yet on the whole the workers have to have awareness, but some of the workers already have the awareness how importance of nature conservation. This shows that YKAY in the process of empowerment has a tendency that emphasizes the process of transferring or providing partial power, strength, and the ability for workers to keep them powerful. Keywords: Community empowerment, conservation / preservation of natural